FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BERKARIR SEBAGAI AKUNTAN PUBLIK PADA MAHASISWA PROGRAM STUDI AKUNTANSI UNIVERSITAS KRISTEN MARANATHA BANDUNG - Vinny Stephanie Hidayat; Enrico Goiyardi (AKURAT | Jurnal Ilmiah Akuntansi FE UNIBBA, 2017)
The aim of this research istodetermine the effectof financial rewards, labor market considerations, and work environment toward thestudent interest on career as an public accountanton accounting student of Maranatha Christian University. The population of this research iswhole of the accounting students of Maranatha Christian University. In this research i took 290 students as a population (the amount of the students i teached in even semester of 2015-2016 and odd semester of 2016-2017). The sample used in this research is 166 students. The methodused in this researchis explanatory research, and thesamplingmethodused wasjudgement sampling method. Research hypothesis testingusing T test, F test, andmultiple regression analysisusingSPSSversion20.0. The results of this research shows that rewards, labor market considerations, and work environment affect thestudent interest on career as an public accountanton accounting student. Thus, the hypothesis of this research is empirically supported.